References to St Augustine in Expositio Symboli Apostolorum by Jan of Kwidzyn - Piechocka-Kłos, Maria (Studia Warmińskie, 2022)
The investigations presented in this paper research concern the Latin manuscript of the Expositio Symboli Apostolorum by Jan of Kwidzyn (b. 1343, d. 1417). The Commentary was probably written between 1399 and 1401 in Kwidzyn, and qualifies as a theological and practical commentary in terms of genres of mediaeval literature. Expositio Symboli consists of a prologue and twelve articles with an appendix. The paper aims to demonstrate how often the work refers to the writings of St Augustine and his thought and provides the particular sources of such references and their purpose. It has been established that Jan of Kwidzyn, whose Commentary is a vessel for his theological views, made relatively frequent use of fragments of the works of St Augustine and his conceptions, with approximately 80 references to over 20 texts by St Augustine in the form of quotations and paraphrases. The paper itself represents an innovative contribution. The findings of this study constitute a substantial addition to medieval studies, as they yield new knowledge about Jan of Kwidzyn as a significant medieval theologian in both Polish and international science.